Salivary alpha amylase and salivary cortisol response to fluid consumption in exercising athletes - TP Backes; PJ Horvath; KA Kazial (Termedia Publishing House, 2015)
The objective of the study was to examine salivary biomarker response to fluid consumption in exercising athletes. Exercise induces stress on the body and salivary alpha amylase (sAA) and salivary cortisol are useful biomarkers for activity in the sympathoadrenal medullary system and the hypothalamic pituitary adrenal axis which are involved in the stress response. Fifteen college students were given 150 ml and 500 ml of water on different days and blinded to fluid condition. The exercise protocol was identical for both fluid conditions using absolute exercise intensities ranging from moderate to high. Saliva was collected prior to exercise, post moderate and post high intensities and analyzed by Salimetrics assays. Exercise was significant for sAA with values different between pre-exercise (85 ± 10 U • ml-1) and high intensity (284 ± 30 U • ml-1) as well as between moderate intensity (204 ± 32 U • ml-1) and high intensity. There was no difference in sAA values between fluid conditions at either intensity. Exercise intensity and fluid condition were each significant for cortisol. Cortisol values were different between pre-exercise (0.30 ± 0.03 ug • dL -1 ) and high intensity (0.45 ± 0.05 ug • dL -1 ) as well as between moderate intensity (0.33 ± 0.04 ug • dL -1 ) and high intensity. Moderate exercise intensity cortisol was lower in the 500 ml condition (0.33 ± 0.03 ug • dL -1 ) compared with the 150 ml condition (0.38 ± 0.03 ug • dL -1 ). This altered physiological response due to fluid consumption could influence sport performance and should be considered. In addition, future sport and exercise studies should control for fluid consumption.